Implementation inside Safeguarding Principles UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage 2003 in Indonesia - Rania Sekar Dahayu; Khoirur Rizal Lutfi (Budapest International Research and Critics University, 2021)
The personality of a nation will be reflected through its culture. Culture is a form of intangible wealth owned by a country. Intangible Cultural Heritage is the cultural heritage of the ancestors that is passed down to the next generation. Intangible Cultural Heritage has cultural, political and economic values. Intangible Property Inheritance has been regulated in the 2003 UNESCO Convention which “Protection” referred to the word